Clinicopathology of graft detachment after Descemet's membrane endothelial keratoplasty. (13th April 2014) - Brockmann, Tobias; Brockmann, Claudia; Maier, Anna‐Karina; Schroeter, Jan; Pleyer, Uwe; Bertelmann, Eckart; Joussen, Antonia M.; Torun, Necip
Abstract Purpose To investigate pathomechanisms involved in graft detachment after Descemet's membrane endothelial keratoplasty (DMEK) and its clinical implications. Methods In a prospective case series, 30 eyes with Fuchs' endothelial dystrophy underwent DMEK. Intraoperatively obtained recipients' endothelium‐Descemet's membranes (EDMs) were investigated histologically and immunohistochemically. The postoperative donor graft status was categorized as attached or detached. Clinical and morphological parameters were analysed between the study groups. Results The detachment rate was 40% (12/30). There was no significant difference in postoperative visual acuity between the groups, but visual recovery was delayed in eyes with initially detached grafts. Gender, age, preoperative central corneal thickness or best corrected visual acuity did not influence the detachment rate. However, separation and disruption of the anterior banded layer (ABL) were frequently observed in patients with graft detachment, and ABL thickness was identified as a significant predictor for graft detachment. The ABL thickness was 2.5 ± 0.9 μm and 3.5 ± 1.6 μm in patients with attached and detached grafts, respectively. Immunohistologically, a deficiency of fibronectin and cytokeratin was observed within the ABL of patients with detached grafts. In contrast, a complete removal of the EDM with residual stromal collagen fragments was observed in patients with adherent grafts. Conclusions Incomplete removal of the EDM, with residual ABL fragments on the recipients' corneal stroma, may be a risk factor for graft detachment after DMEK. The separation and disruption of the ABL might be promoted by a deficiency of matrix proteins, stronger biomechanical properties and a firm adherence to the posterior corneal stroma.